A case of colonic gallstone ileus with a spontaneous evacuation - Bajracharya, A; Pathania, OP; Adhikary, S; Agrawal, CS (Health Renaissance, 2011)
Colonic gallstone is an uncommon entity with a high morbidity and mortality due to various reasons. It remains a diagnostic challenge because of delayed and non-specific presentations, especially in the elderly population, often with multiple co-morbidities. We present a case of colonic gallstone ileus with spontaneous evacuation in a 67 years female who had a threeday history of intermittent bouts of colicky abdominal pain, vomiting , constipation and progressive abdominal distension, features of large bowel obstruction treated non operatively for 72 hours and passage of the stone spontaneously. Keywords: gallstone ileus; large bowel obstruction; colonic gallstone DOI: 10.3126/hren.v9i1.4363 Health Renaissance, 2011: Vol.9 No.1:47-49